The interplay between antimicrobial resistance, heavy metal pollution, and the role of microplastics - Balta, Igori; Lemon, Joanne; Gadaj, Anna; Cretescu, Iuliana; Stef, Ducu; Pet, Ioan; Stef, Lavinia; McCleery, David; Douglas, Alastair; Corcionivoschi, Nicolae (Frontiers in Microbiology, 2025)
Environmental pollution with heavy metals (HMs) and microplastics (MPs) could enhance the global health challenge antimicrobial resistance (AMR). Herein, we explore the complicated mechanics of how HMs, MPs, and AMR are interlinked within microbial ecosystems, as well as the co-selection and cross-resistance mechanisms. Unlike antibiotics, HMs have influenced microbial evolution for billions of years, promoting resistance mechanisms that predate antibiotic resistance genes (ARGs). At the same time, this conundrum is further complicated by the pervasive spread of MPs in the aquatic and terrestrial environments, acting as substrates for bacterial pathogenic biofilms and accelerates the horizontal gene transfer (HGT) of ARGs and heavy metal resistance genes (MRGs). This review highlights that HMs such as lead (Pb), mercury (Hg), arsenic (As), chromium (Cr), cadmium (Cd), and nickel (Ni) have persistently selected for resistance traits through efflux systems and genetic co-regulation. Together, these interactions are amplified by MPs that create genetic exchange hotspots due to biofilm formation. These dynamics are modulated by organic matter, which serves both as a nutrient source and a mediator of HM bioavailability, directly influencing ARG abundance. Soil and water ecosystems, including riverine systems and landfill leachate, are reservoirs for ARGs and ARG–MRG combinations, with notable contributions originating from anthropogenic activities. This review also emphasizes the urgent need for integrated environmental and public health strategies to mitigate pollutant-driven AMR. This work seeks to approach HMs and MPs as synergistic drivers of AMR such that both HMs and MPs are upstream (causes) levers, a foundation from which future research on sustainable environmental management practices and health policy (One Health Approach), aimed at curbing the spread of resistance determinants can proceed.